PENERAPAN ALGORITMA DECISION TREE UNTUK KLASIFIKASI KONSUMSI ENERGI LISTRIK RUMAH TANGGA DENGAN PENGGUNAAN RAPIDMINER - Ubeitul Maltuf; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
The research aims to explore and understand energy consumption patterns in households. By using the Decision Tree algorithm, to classify the level of electrical energy consumption. And data on household electrical energy consumption can be obtained from various sources, such as Household electricity meter. Survey or questionnaire filled out by homeowners regarding the use of electrical appliances. Based on the image above, the application of the Decision Tree algorithm in analyzing risk factors for The classification of household electrical energy consumption produces an accuracy value of 100.00%. From the displayed confusion matrix, we can see the distribution of predicted and actual values for various classes. For example, in the class